Konsep Kebijakan Dan Perencanaan Strategis Dalam Pendidikan - Mochamad Chairuddin (Jurnal Ilmu Pendidikan Islam, 2023)
The literature research study discusses the importance of policy concepts and strategic planning in the context of education as the foundation for a nation's progress. The two are interrelated, with policy providing direction and purpose, while strategic planning implements action plans. Educational policy forms an education system's principal foundation, while strategic planning identifies long-term goals and allocates resources to achieve desired outcomes. Effective policy implementation provides the basis for successful strategic planning by validating policies and guiding strategy with relevant data. This process helps adjust plans and resource allocation according to actual needs, ensures consistency between policy objectives and implemented systems, and increases the potential for achieving desired educational goals. In this research, the main focus is an in-depth analysis of the relationship and contribution of the two in advancing education.